Constituintes químicos das partes aéreas de Baccharis retusa (Asteraceae) – identificação e avaliação de atividade biológica - Ueno, Anderson Keity [UNIFESP] (2017)
In this present work a phytochemical study of nonpolar extract from the aerial parts of Baccharis retusa (Asteraceaee) and antiparasitic evaluation from its purified compounds have been done. Chromatography techiniques was employed for the purification of the crude extract and its following fractions and for the substance description it was selected spectroscopy/spectrometric techniques like NMR and MS. It has been detected three sesquitepenes: -cadinene (A), caryophyllene oxide (B) and humulene oxide (C), three diterpenes ent –kaur-16-ene (D), ent kaurenoic acid (E), 15-β-senecioyloxy-ent-kaur-16-en-19-oic acid (F), the flavonoid sakuranetin (G) and two C6C3 derivatives substances named trans hexacos-18-enyl cumarate (H) and cis hexacos-18-enyl cumarate (I). The values off CC50 displayed on NCTC for compounds E, G, H and I were superior than 200 μM while F was 189,7 μM. The SI values for compouds E and F for antichagasic were higher than 7 and 49 respectively, these results demonstrate that the latter compound has an excellent potencial against T. cruzi trypomastigotes once the standard compound benznidazole has an SI lower (10) than the tested compounds. These results notably contributes on phytochemistry issues for genus Baccharis, besides it is also a source of natural compounds that has biological activities, specially compound F which have been only detected on B. illinita until this presente moment.